Exploring the Genomic Architectures of Health, Physical Traits and Antisocial Behavioral Outcomes: A Brief Report - Tielbeek, Jorim J.; Boutwell, Brian B. (Frontiers in Psychiatry, 2020)
A widely replicated finding across the behavioral sciences is that antisocial behavior in general, and criminal behavior in particular, correlate with an array of health problems. Less clear, however, is the precise nature of this association. There is likely strong reason to suspect that a direct causal link exists between incarceration—a consequence of some antisocial behaviors—and certain negative health outcomes, for instance. However, it might be the case that broader phenotypes like antisocial behavior may correlate with certain health traits at a genomic level. We explore this possibility from a theoretical vantage point, while also presenting some preliminary data from existing secondary sources. Tentatively, no significant genetic correlations emerged across a host of health and wellbeing outcomes, suggesting limited genomic overlap at this point. However, more work is needed exploring this topic. We propose that future studies should make use of larger, more diverse samples and examine the genetic overlap between homogeneous clusters of antisocial behavioral subtypes and disease traits or symptoms.